MENGEKSTRAK PARAMETER FISIS DARI DATA OBSERVASI (Contoh Kasus Percepatan Gravitasi Bumi) - Muhammad Hamzah Syahruddin (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2015)
Almost the entire data field of geophysical surveys requires inversion to obtain physical parameters and models. The purpose of this study is to extract the unknown variables (unknown variable) and the physical parameters of the unknown (unknown parameters) of the data field observations. Examples of case studies, is a free fall motion. Measurement of geophysical data is data height (h) and travel time (t). By doing mathematical modeling of observation data can be obtained relationship between h and t. Furthermore, the mathematical models do inversion to get the physical parameters of the unknown. From these physical parameters can be made geophysical modeling. Based on the experimental design and inversion modeling results obtained initial height (ho) is 1.5 meters, the initial velocity (vo) is 6.28099 m / s, and the Earth's gravitational acceleration constant (g) is 9.8 m / s2 Keywords: experiential learning, Mathematical models, physical parameters, inversion modeling.